Inside Cover: Construction of Highly Ordered Glyco‐Inside Nano‐Assemblies through RAFT Dispersion Polymerization of Galactose‐Decorated Monomer (Angew. Chem. Int. Ed. 20/2021). Issue 20 (8th March 2021) - Qiu, Liang; Zhang, Haoran; Bick, Thomas; Martin, Johannes; Wendler, Petra; Böker, Alexander; Glebe, Ulrich; Xing, Chengfen
Abstract : An efficient strategy for constructing glyco‐inside nano‐assemblies is presented by Liang Qiu, Ulrich Glebe, Chengfen Xing et al. In their Communication on page 11098, a series of highly ordered glyco‐inside nano‐assemblies derived from sugar‐decorated block copolymers were obtained via PISA induced by RAFT dispersion polymerization of a galactose‐decorated monomer.